A REVISED CLASSIFICATION OF CYNODONTS (REPTILIA; THERAPSIDA) - Hopson, James A.; Kitching, James W. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1972)
Cynodonts are very advanced mammal-like reptiles of the Permian-Triassic which are of special interest to evolutionists because they gave rise to the Class Mammalia during Middle or Late Triassic time. Cynodonts have been known from strata of Early Triassic age in South Africa for over one hundred years, and numerous specimens have been collected and described. In recent years the record of cynodonts has been extended into earlier and later time zones, not only in southern Africa but in East Africa, South America, Russia , China, and, most recently, in North America. Much of the material from outside of Africa has not yet been fully described.